Memory, Dance and Archive: How an Archived Performance Inspired the Creation of the Dancefilm Does the Dancing Have to Stop? - York-Pryce, Sonia Davina (The International Journal of Screendance, 2022)
The aim of this article is to delve into memory and dance, and to show how the archive can contribute to definitions of dance. It offers a personal journey into the records of my dance career, where I revisit and reclaim the past framed through the perspective of a mature dancer now aged in my sixties. Using the medium of dancefilm, my position is of observer, dancer, recaller, and bearer of my archive. I experiment with traces of the past, overlaid with the present, to introduce a dialogue about how this investigation can address the aging body as a site of archive. Through my research, I assert that as a dancer, my archive is housed within my body. I am using my dance history and my memories as the vehicle to address the issue of aging from a Western dance context.